Seeking, Place, and Recognition in the Gospel of John: A Narrative and Theological Exploration of the Three Zētein-Dialogues. - Danbolt, Lars Johan; Wang, Øystein (Studia Theologica, 2025)
This article investigates three structurally parallel dialogues in the Gospel of John (1:37–39; 18:3–9; 20:14–17), each initiated by a form of the verb zētein ("to seek"), culminating in distinct acts of recognition, and occurring at the beginning of new narrative sections – namely, Jesus' ministry, legal proceedings, and post-resurrection stories. While the motifs of seeking and recognition are well established in Johannine scholarship, this study offers a focused narrative and theological analysis of what is termed the zētein-dialogues, emphasizing their shared structure: Jesus initiates a dialogue with a zētein question, the interlocutors respond with a reference to place, and Jesus reveals his identity in different ways – inviting, manifesting, and relating. Drawing on narrative criticism and informed by parallels with Greek tragedy, the article argues that these dialogues function as narrative thresholds that both frame and advance the gospel's Christological agenda. Furthermore, the motifs of seeking, place, and recognition are shown to resonate with broader theological concerns related to divine identity, presence, and human response, making the zētein dialogues a valuable interpretive lens for understanding the Gospel of John.